Does Sleep Really Matter? Examining Sleep among Salespeople as Boundary Role Personnel for Key Job Factors. Issue 1 (2nd January 2020) - Edmondson, Diane R.; Matthews, Lucy M.
ABSTRACT: Purpose: Sleep deprivation among employees has become commonplace in the workforce. In the United States, the number of hours individuals sleep per night has declined by an hour and a half per night since the 1960s. As of 2005, seventy-four percent of individuals were getting less than eight hours of sleep per night on weekdays. There are negative ramifications to the organization when employees are sleep deprived such as lost productivity, increased accident rate, and increased absenteeism. Originality/Value/Contribution of the paper: Although prior research has investigated the impact that sleep deprivation has on unique job positions (e.g., shift workers, transportation), no research has investigated how sleep impacts business-to-business sales employees. Due to the responsibilities of business-to-business sales employees, this type of position should not just be lumped in with other organizational employees. For example, business-to-business sales employees are boundary spanning employees that are responsible for generating revenue for the organization. These sales employees are also more likely to be physically, socially, and psychologically separated from the organization since they frequently work outside of the office. Because of these distinctive roles, this study examines if differences based on sleep duration exist for business-to-business sales employees for two individual and five organizational factors. The two individual factors consisted of grit and happiness while the five organizational factors consisted of perceived organizational support, perceived supervisory support, job satisfaction, organizational commitment, and turnover intentions. Methodology/Approach: Data was collected from 320 business-to-business sales employees using a cross industry survey. The survey was conducted using a Qualtrics panel. Sleep duration was broken into two groups with one group consisting of business-to-business sales employees who sleep, on average, seven or more hours per night and the other group consisting of business-to-business sales employees who sleep, on average, six or less hours per night. The sleep duration groups were determined based on prior research that found adults should regularly sleep seven or more hours per night in order to support optimal health. There were one hundred thirty-four respondents who slept six hours or less and one hundred eighty-six respondents who slept seven or more hours, on average, per night. Findings: The research question developed was answered by examining the differences between means for the two individual constructs and the five key organizational constructs. Differences in sleep duration for six of the seven sales constructs. There were significant differences between those that slept seven or more hours per night from those that slept six or less for grit, perceived organizational support, perceived supervisory support, job satisfaction, organizational commitment, and turnover intentions. Results found that business-to-business sales employees that slept seven or more hours per night exhibited more grit than those that slept six or less hours per night. In addition, business-to-business sales employees that slept six or less hours per night had higher perceptions of both organizational and supervisory support than those that slept seven or more hours per night. Furthermore, business-to-business sales employees that slept six or less hours per night displayed higher job satisfaction and organizational commitment than sales employees that slept seven or more hours per night. Finally, business-to-business sales employees that slept seven or more hours per night indicated higher levels of turnover intentions than sales employees that slept six or less hours per night. There were no significant differences between the two sleep groups for sales employee happiness. Although some of these results may appear to be counterintuitive, conservation of resources theory can be used to explain these findings. Research Implications: This exploratory study showcases the importance of good sleep among business-to-business sales employees. This study draws on the conservation of resources theory literature to explain the counterintuitive findings. This theory posits that individuals will retain and guard against resource depletion. Additionally, as resources become depleted, other resources are valued to a greater extent. In this study, the resource being depleted is the condition of sleep. When business-to-business sales employees experience a lower average amount of sleep per night (i.e., six hours or less), they perceive higher levels of support, job satisfaction, and organizational commitment than business-to-business sales employees who experience a higher average amount of sleep per night (i.e., seven hours or more). Although this study provides a good initial examination of how sleep impacts sales organizations, this study also highlights the need for additional business-to-business sales employee sleep research. This is the first study that has examined how sleep duration impacts business-to-business sales employees. Practical Implications: This study is important to sales research because it highlights the impact that poor sleep of business-to-business sales employees has on the organization. For sales organizations, we provide guidance on ways a sales organization can help promote healthy sleep for their business-to-business sales employees. Some examples of guidance provided can be categorized into four primary categories. These categories include (1) proper sleep education, (2) sales management training, (3) creating a sleep friendly workplace environment, and (4) creating specific workplace policies to minimize sleep disturbances such as setting reasonable work hours and sleep accommodating travel schedules.